DEVELOPMENT AND VALIDATION OF A NOVEL AUTOMATED SYSTEM FOR STREAMLINING SPECIMEN PROCESSING AND ENHANCING LABORATORY WORKFLOW EFFICIENCY - Bander Ali Almutairi, Ahmed Haif Aldheferi, Ahmed Masod Alshammri, Jaber Ahmed Alshammari, Nawaf Mohammed Albadrani, Younis Aliwi Al-Anazi , (Chelonian Research Foundation, 2022)
Clinical laboratories play a crucial role in the healthcare system by providing accurate and timely diagnostic information to support patient care. However, the increasing demand for laboratory services, coupled with the need for efficient resource utilization, has led to a growing interest in automated systems that can streamline specimen processing and enhance laboratory workflow efficiency. In Saudi Arabia, the adoption of such systems has been limited, and there is a paucity of research on their development and validation in the context of the country's clinical laboratories. This study aims to address this gap by developing and validating a novel automated system for specimen processing and assessing its impact on laboratory workflow efficiency in a large clinical laboratory in Saudi Arabia. The research will be conducted by a team of laboratory technicians, including BANDER ALI ALMUTAIRI, AHMED HAIF ALDHEFERI, AHMED MASOD ALSHAMMRI, JABER AHMED ALSHAMMARI, Nawaf Mohammed Albadrani, and Younis Aliwi Al-Anazi. Their expertise in clinical laboratory practices and automation will be invaluable in designing, implementing, and evaluating the novel automated system. The study will employ a mixed-methods approach, combining quantitative data analysis of specimen processing metrics and qualitative data from user feedback. The development of the automated system will involve requirements gathering, system design, and prototype development. The system will be designed to integrate specimen sorting, centrifugation, aliquoting, and labeling functions, with the goal of optimizing workflow efficiency and minimizing the risk of errors. The validation phase will involve the implementation of the system in the participating clinical laboratory, followed by data collection and analysis to assess its impact on specimen processing efficiency and laboratory workflow. The findings of this study are expected to demonstrate significant improvements in turnaround times, error rates, and throughput after the implementation of the automated system. The qualitative data from user feedback will provide valuable insights into the usability, benefits, and challenges of the system. The study's results will have important implications for laboratory management and patient care in Saudi Arabia, highlighting the potential of automated systems to streamline specimen processing and enhance laboratory workflow efficiency. This research will contribute to the growing body of evidence on the benefits of automated specimen processing systems and provide guidance for their adoption and implementation in Saudi Arabian clinical laboratories. The findings will be of interest to laboratory professionals, healthcare providers, and policymakers seeking to improve the quality and efficiency of laboratory services in the country. The authors will recommend further research to evaluate the long-term impact of automated systems on laboratory performance and patient outcomes and to explore the potential for integrating advanced technologies into specimen processing workflows. In conclusion, this study represents a significant step forward in the development and validation of automated systems for streamlining specimen processing and enhancing laboratory workflow efficiency in Saudi Arabia. The novel automated system developed by the team of laboratory technicians has the potential to transform the way clinical laboratories operate in the country, ultimately improving the quality and timeliness of diagnostic services and supporting better patient care.